City of secrets - Ying, Victoria (Viking, 2020)
Orphan Ever Barnes spends his days roaming the Switchboard Operating Facility, but his life is turned upside down when he meets Hannah, the daughter of the building's new owner. They soon embark on an adventure to learn the secrets of the mechanical building and find themselves in a world filled with secret societies, assassins, codes, and maps.